(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This research paper critically examines Raymond Williams' theory of cultural materialism—a framework that reconfigures the traditional Marxist view of culture by emphasizing its dynamic, processual nature. By analyzing Williams' key texts and concepts, such as the interrelation of culture and society, the notions of residual, dominant, and emergent cultures, and the idea of "structures of feeling," the paper elucidates how cultural materialism offers a nuanced understanding of cultural production and transformation. The analysis situates Williams' contributions within the broader spectrum of cultural studies, discusses their enduring relevance, and considers both the theoretical innovations and limitations of his approach in addressing contemporary socio-cultural phenomena.